Neurodevelopmental and Psychosocial Outcomes in Adolescence of Children with Early Diagnoses of ADHD, Autism, Dyscalculia and Dyslexia. - Cai, Yufei; Holmes, Joni; Michelini, Giorgia; Eley, Thalia C.; Gathercole, Susan E. (Research on Child & Adolescent Psychopathology, 2025)
The study examined neurodevelopmental and psychosocial outcomes in adolescents aged 12 and 16 with childhood diagnoses of ADHD, autism, dyscalculia, or dyslexia. Participants were drawn from the Twins Early Development Study based on parent-reported diagnoses between ages 7 and 9 of ADHD (n = 54), autism (n = 50), dyscalculia (n = 282), and dyslexia (n = 695). A comparison group included 6,882 participants without neurodevelopmental diagnoses. Differences in ADHD and autistic traits, academic challenges, peer difficulties, and internalizing issues were explored between the comparison group and each neurodivergent group at ages 12 and 16. Across timepoints, neurodivergent groups showed distinct patterns of difficulties across domains relative to the comparison group. The ADHD group had higher levels of inattention and hyperactivity/impulsivity at 12 and 16, lower academic performance at 16, and elevated mental health challenges at 12. The autism group showed higher degrees of inattention, hyperactivity/impulsivity, autistic traits, and peer difficulties at 12 and 16. The dyscalculia group had challenges in all domains except for peer relationships at 12, with only mathematical underachievement persisting to 16. The dyslexia group showed difficulties in all domains at 12 with issues related to inattention, hyperactivity/impulsivity, academic achievement, and peer relationship persisting to 16. Whereas at age 12 the neurodivergent groups showed diagnosis-specific difficulties and broader neurodevelopmental and psychosocial challenges, by age 16 they were characterized by distinctive trajectories with persisting and resolved difficulties. These findings underscore the need for repeated, broad-based assessments to understand the changing needs of children with early neurodevelopmental diagnoses.